Quem é Este? Poder, Medo e Identidade Mítica na Narrativa de Marcos 4. 35 41 - Magajewski, Carlos Guilherme Fagundes da Silva (2010)
This dissertation offers an exegesis of Mark 4. 35 41, Jesus Stills a Storm . Towards that goal, it starts with a critical survey of the current Quest for the Historical Jesus in dialogue with Cultural History, Microhistory and Historical Psychology, with the aim of raising relevant issues pertaining mythical narratives as well as their inherent value for our historical knowledge. From the literary mapping of the Greek Magical Papyri, and from evidence stemming from Qumran s Self Glorification Hymn , as well as the Old Testament and the later rabbinical texts arise fundamental parallels that are critical for our understanding of said narrative. Thus, the exegesis of our pericope sheds light on the elements of power, fear and mythical identity present in the narrative.(AU)